2008
DOI: 10.1186/1471-2415-8-19
|View full text |Cite
|
Sign up to set email alerts
|

Refractive change following pseudophakic vitrectomy

Abstract: Background: To assess the occurrence and magnitude of refractive change in pseudophakic eyes undergoing 20 gauge pars plana vitrectomy without scleral buckling and to investigate possible aetiological factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 13 publications
2
29
1
7
Order By: Relevance
“…Studies including various vitreoretinal pathologies found refractive changes between )0.30 (Kumagai et al 2001) and )0.45 D (Byrne et al 2008) in pseudophakic vitrectomy. These studies also included patients with intraocular gas tamponade.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Studies including various vitreoretinal pathologies found refractive changes between )0.30 (Kumagai et al 2001) and )0.45 D (Byrne et al 2008) in pseudophakic vitrectomy. These studies also included patients with intraocular gas tamponade.…”
Section: Discussionmentioning
confidence: 96%
“…The ACD increases following vitrectomy in phakic eyes (Akinci et al 2008). Vitrectomy in pseudophakic eyes has been reported not to change the ACD (Byrne et al 2008).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Показано, что после хирур-гии катаракты глубина передней камеры увеличивается примерно на 1,4 мм [37,38], из-за этого ELP отодвигается назад. Витрэктомия на факичных глазах также способ-ствует смещению ELP назад [39], а на афакичных глазах не меняет ELP [40], что можно объяснить ее предше-ствующим смещением назад после удаления катаракты. С другой стороны, после факовитрэктомии ИОЛ смеща-ется назад даже в большей степени, чем после изолиро-ванной хирургии катаракты [41][42][43].…”
Section: осложненияunclassified
“…В другом исследовании, включавшем 84 пациента, S. Byrne и соавт. [14] наблюдали усиление рефракции через 4 мес после витрэктомии. В 61 из 87 артифакичных глаз отмечен миопический сдвиг в среднем на (-) 0,5 дптр.…”
unclassified